2008
DOI: 10.1002/jts.20303
|View full text |Cite
|
Sign up to set email alerts
|

The internalizing and externalizing structure of psychiatric comorbidity in combat veterans

Abstract: This study examined the latent structure of psychiatric disorders in a sample with a high prevalence of PTSD. A series of confirmatory factor analyses tested competing models for the covariation between Structured Clinical Interview for DSM-III-R diagnoses among 1,325 Vietnam veterans. The best-fitting solution was a 3-factor model that included two correlated internalizing factors: anxious-misery, defined by PTSD and major depression, and fear, defined by panic disorder/agoraphobia and obsessive-compulsive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
108
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 42 publications
(69 reference statements)
15
108
1
Order By: Relevance
“…Consistent with Hypothesis 1, a three-factor solution similar to one previously identified among male Vietnam veterans (Miller et al, 2008) was found to demonstrate close fit to the data in both samples. As expected, alcohol-use disorders, substance-use disorders, and nicotine dependence loaded onto the externalizing-SUD factor, PTSD and depression loaded onto the distress factor, and panic disorder, social phobia, specific phobia, and OCD loaded onto the fear factor.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with Hypothesis 1, a three-factor solution similar to one previously identified among male Vietnam veterans (Miller et al, 2008) was found to demonstrate close fit to the data in both samples. As expected, alcohol-use disorders, substance-use disorders, and nicotine dependence loaded onto the externalizing-SUD factor, PTSD and depression loaded onto the distress factor, and panic disorder, social phobia, specific phobia, and OCD loaded onto the fear factor.…”
Section: Discussionsupporting
confidence: 79%
“…First, given the well-documented relationship between the externalizing-SUD dimension, antisocial personality disorder, and impulsivity problems (e.g., Miller et al, 2008) as well as prior research associating alcoholand substance-use problems with violence among returning veterans (Elbogen et al, 2008;MacManus et al, 2012), it is surprising that violent behavior was not at least modestly associated with the externalizing-SUD dimension; however, as can be seen in Figure 2, when violence was regressed onto both factors, the externalizing-SUD factor had almost no effect on violence (β = 0.03) across samples. Moreover, constraining the path from externalizing-SUD to difficulty controlling violent behavior to be zero did not affect model fit significantly in either sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors scores were correlated, but only the externalizing factor was uniquely related to self-report of aggression over the past year. Though previous research has provided support for applying an internalizing/externalizing distinction to understanding heterogeneity in the presentation of patients with PTSD (Miller, 2003;Miller et al, 2003Miller et al, , 2004Miller et al, , 2008Miller et al, , 2012, to our knowledge this is the first report to (1) assess the internalizing/externalizing dimensions of posttraumatic stress and associated comorbidity as measured by the PAI and (2) demonstrate the incremental contribution of externalizing psychopathology in the measurement of aggressive behavior.…”
Section: Discussionmentioning
confidence: 85%
“…While these studies have supported the internalizing/externalizing distinction as a useful heuristic for studying the structure of posttraumatic psychopathology, they are limited by a reliance on cluster-analytic models which are not optimal for examining higher order factor structure of psychopathology thought to be dimensional (Miller, Fogler, Wolf, Kaloupek, & Keane, 2008).…”
Section: Va Author Manuscriptmentioning
confidence: 99%